Propuesta de implementación de un Sistema de Control Interno – SCI para la optimización de las actividades asociadas al área de tesorería en la empresa C.I Tequendama SAS en la ciudad de Santa Marta - Castro Martínez, Adaluz; Hernández, Stephen (Universidad Antonio Nariño, 2023)
The design and implementation of an integrated internal control system at the organizational level become relevant factors for the fulfillment of organizational objectives, thereby allowing the strengthening of planning and optimization schemes at the level of strategic procedures. If the business objective is to guarantee a sustainable competitive model, the importance of implementing periodic reviews of the execution mechanisms in different areas must be recognized, and propose regulatory frameworks that direct each of the actions that must be carried out by those responsible for these tasks. , especially in accounting and financial jobs. The objective of this document is to implement an Internal Control System – SCI for the optimization of accounting activities associated with the treasury area in the company C.I Tequendama SAS in the city of Santa Marta. To carry out this research prospectus, a qualitative descriptive methodology was used, since the procedures of the treasury area of the company in question could be observed, and technical conclusions were obtained thanks to the application of a recognition matrix where they were analyzed. different informative aspects regarding processes and application methodologies using the COSO I audit model.